СТРУКТУРНО-СТИЛЬОВИЙ ПІДХІД ДО ОРГАНІЗАЦІЇ ОСОБИСТІСНО-ЗОРІЄНТОВАНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2007)
The article covers the issues of correlation between normative and creating in the conditions of module-sectional organizations of educational information on creative faculties and priorities of realization of structural-stylish approaches to organization of the personality-oriented teaching of future teachersartists.